Ambient and Heat-Cured Geopolymer Composites: Mix Design Optimization and Life Cycle Assessment - Mohamed Rabie (Sustainability, 2022)
The feasibility of producing sustainable cement-free composites and its environmental impact were investigated in this research. Experimental parametric evaluation was carried out in this regard to explore the optimum mix design of the composites. The effect of synthesis parameters and curing conditions on the behavior of the produced geopolymer composites was investigated. The studied parameters included the molarity of the sodium hydroxide solution (12 M, 14 M, and 16 M), the sodium silicate to sodium hydroxide ratio (1, 1.5, 2, and 2.5), the fluid to binder ratio (0.6, 0.65, and 0.7), and the age. The curing conditions included ambient curing and heat treatment at 40 °C, 80 °C, and 120 °C for 24 h, 48 h, and 72 h. In addition, life cycle assessment was performed to compare the environmental impact of geopolymer and cementitious composites. The results reflected the possibility of producing geopolymer composites with significant positive environmental impacts over traditional cementitious composites. The synthesis parameters played a major role in the behavior of the produced geopolymers. Heat curing was necessary for the geopolymer mortar to achieve high early strength. However, strength development with age was more obvious for ambient-cured specimens than heat-cured specimens. The optimum fluid to binder ratio used in this research was 0.6. For this ratio, the compressive strength increased as the molarity of the sodium hydroxide solution increased for all sodium silicate to sodium hydroxide ratios. Finally, SEM images showed that the higher the molarity and as the amount of reacted FA particles increased, the better the microstructure of the geopolymer mortar was and the fewer pores the matrix had.